Tuberous Sklerosis Kompleks Pada Pasien Wanita Usia 22 Tahun - Desi Novianti; Audrina Ernes (PRIMER (Prima Medical Journal), 2023)
Backgrounds: Tuberous sclerosis complex (TSK) is an autosomal dominant disorder that predisposes to the development of benign lesions in several organs of the body especially in the brain, kidneys, liver, skin, heart and lungs. Subependymal giant cell astrocytoma (SEGA) is a characteristic brain tumour that occurs in 10%-20% of patients with tuberous sclerosis complex and is almost exclusively associated with tuberous sclerosis complex. Objective: Demonstrate the role of radiological imaging (CT scan and MRI) in determining the diagnosis and as a reference for determining subsequent therapy in patients with seizures et causa tuberous sclerosis. Case: This case report describes a 22-year-old female patient with a main symptom of frequent headaches since the last 2 months and decreased vision and fogginess in both eyes. The patient has a history of seizures from the age of 4 years to the age of 11 years. Discussion: Four major signs of TSK were found: facial angiofibroma, tuberous sclerosis, subependymal nodule, and subependymal giant cell astrocytoma. Conclusion:  The role of radiological imaging, both CT scan and MRI in the early diagnosis of patients with TSK is very important.